The Inheritance and Change of the Contemporary Daur Shaman - Sa, Minna (Religions, 2019)
The Daur people are a minority living in Northeast China. They have adhered to a form of shamanism since ancient times. They believe that all things are spiritual. The Daur call an intermediary or messenger between the human world and the spirit worlds jad’ən (shaman). In addition, there are also different types of priests and healers, such as baɡʧi (healer and priest), barʃ (bone-setter), ʊtʊʃi (healer of child) and baræʧen (midwife), but only the jad’ən is a real shaman. The Daur’s system of deities is huge, complex, and diverse, mainly including təŋɡər (God of Heaven), xʊʤʊr barkən (ancestral spirit), njaŋnjaŋ barkən (Niang Niang Goddess), aʊləi barkən (spirit of mountain), nuʤir barkən (spirit of snake), ɡali barkən (God of Fire), etc. Among them, ancestral spirit is the most noble and important deity of the Daur, called xʊʤʊr barkən (spirit of ancestors). In the past, the social structure of the Daurs was based on the equal clan xal and its branches mokun. Xʊʤʊr barkən is the ancestral spirit of the mokun family. The shaman with xʊʤʊr barkən as the main patron is called xʊʤʊr jad’ən, that is, mokun shaman. The inheritance of the Daur shaman is very complicated. The xʊʤʊr jad’ən is strictly inherited along the patrilineal line, while the ordinary jad’ən can also inherit according to the maternal lineage. The inheritance rites of other types of shamans are also based mainly on the patrilineal lineage and occasionally the maternal lineage. The complexity of the Daur shaman inheritance is first and foremost related to the variety of the gods and spirits, secondly to their belief of polytheism, and finally to the constant split of the traditional clans and families, namely, the xal-mokun social structure.